An awakening in the force—The birth of ERCSP - Shane P., Desselle (2021)
Many readers of this editorial will recall not so long ago when scholars in pharmacy practice and social pharmacy (PPSP) had very few options to which they might submit papers emanating from their scholarly work. This conundrum only seemed to worsen with notification that Journal of Social and Administrative Pharmacy (JSAP) had published its final issue back in 2003. However, the tide began to turn shortly thereafter, given the confluence of a number of events.